1994
DOI: 10.1128/aac.38.7.1541
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of zidovudine phosphorylation in peripheral blood mononuclear cells from patients infected with human immunodeficiency virus

Abstract: As part of an effort towards optimization of dosing of zidovudine (ZDV), formation and elimination of total phosphorylated ZDV (ZDVPt) in peripheral blood mononuclear cells were examined in 21 asymptomatic human immunodeficiency virus-infected patients during their first 24 weeks of therapy (AIDS Clinical Trials Group Protocol 161). Intracellular concentrations of ZDVPt were measured with a previously described and validated radioimmunoassay technique. Although ZDV phosphorylation occurred readily upon initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…Consistent with our findings, some studies have shown an association between gender and levels of intracellular metabolites of NRTIs (1). Some of these studies report higher rates of toxicity and effective antiviral response in women than in men (1,22,44), while others report the opposite (3,6). In other studies, response rate and survival were not dependent on gender but, rather, were dependent on individualized dose adjustments (9,43).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with our findings, some studies have shown an association between gender and levels of intracellular metabolites of NRTIs (1). Some of these studies report higher rates of toxicity and effective antiviral response in women than in men (1,22,44), while others report the opposite (3,6). In other studies, response rate and survival were not dependent on gender but, rather, were dependent on individualized dose adjustments (9,43).…”
Section: Discussionsupporting
confidence: 79%
“…However, no ethnic difference in the concentrations of intracellular metabolites of NRTIs has been reported to date. Our finding that there is no association between ethnicity and intracellular accumulation of NRTIs is consistent with that of others (44).…”
Section: Downloaded Fromsupporting
confidence: 82%
“…69 Another study also found higher ZDV phosphates (MP plus DP plus TP) among 5 women versus 16 men (1.4-fold; P < 0.01), and a third study found higher 3TC-TP in female compared with male infants despite similar plasma concentrations (1.8-fold; P = 0.04). 61,81 However, a separate study found lower ZDV-triphosphates in female compared with male adults although plasma concentrations were similar. 82 An in vitro study evaluated the effects of progesterone, estrogen, and testosterone on conversion of ZDV and 3TC to ZDV-TP and 3TC-TP in PBMCs and found no major effects, but some minor lowering on 3TC-TP for progesterone and testosterone (all differences were below 50% versus control).…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%
“…In one study, women had statistically higher intracellular zidovudine and lamuvidine triphosphate concentrations compared with men enrolled in the clinical trial, and were noted to suppress their HIV RNA level to less than 50 copies/ml twice as fast as men [18]. In a second Phase I study of the pharmacokinetics of total zidovudine phosphates (the sum of the mono-, di-and tri-phosphates in peripheral blood mononuclear cells), women's mean total zidovudine phosphate area under the curve was 45% higher compared with men [19]. A third study had conflicting results for zidovudine and found that men exhibited significantly higher zidovudine-monophosphate and zidovudine-triphosphate exposure following zidovudine oral administration compared with women [20].…”
Section: Sex Influence On Pharmacokinetic Profilesmentioning
confidence: 99%
“…NRTIs are considered to be prodrugs, since their active moiety is the triphosphate anabolite that is formed intracellularly [16]. NRTI pharmacokinetic information is limited because of the difficult procedures needed to measure NRTI anabolites [17], but four studies have been performed investigating relationships between intracellular nucleoside triphosphate concentrations, sex and ARV response among persons taking zidovudine, lamivudine or abacavir [18][19][20][21]. In one study, women had statistically higher intracellular zidovudine and lamuvidine triphosphate concentrations compared with men enrolled in the clinical trial, and were noted to suppress their HIV RNA level to less than 50 copies/ml twice as fast as men [18].…”
Section: Sex Influence On Pharmacokinetic Profilesmentioning
confidence: 99%